2015
DOI: 10.1136/bmjquality.u206142.w2524
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recovery programme in gynaecology: outcomes of a hysterectomy care pathway

Abstract: There was a wide variation in the peri-operative management of women undergoing hysterectomy for both benign and malignant disease at Southend University Hospital NHS Foundation Trust prior to 2010. The median length of stay following a hysterectomy and more radical gynaecological oncology surgery was five days and seven days respectively. The NHS East of England Strategic Health Authority commissioned the development of Enhanced Recovery Programme (ERP) in various surgical specialties including gynaecology an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Overall, the response to the ERAS protocol was positive for open, laparoscopy, and vaginal surgery. Patient satisfaction was high in all studied aspects of perioperative care for the ERAS groups, including patient education, quality of care during hospitalization, pain management, coordination of care, and discharge process, but no scores were available for the historical control subjects [12,17,27]. For Kalogera et al [27] the lowest satisfaction was regarding PONV, with only 87% rating it as excellent or very good.…”
Section: Patient Satisfactionmentioning
confidence: 97%
See 3 more Smart Citations
“…Overall, the response to the ERAS protocol was positive for open, laparoscopy, and vaginal surgery. Patient satisfaction was high in all studied aspects of perioperative care for the ERAS groups, including patient education, quality of care during hospitalization, pain management, coordination of care, and discharge process, but no scores were available for the historical control subjects [12,17,27]. For Kalogera et al [27] the lowest satisfaction was regarding PONV, with only 87% rating it as excellent or very good.…”
Section: Patient Satisfactionmentioning
confidence: 97%
“…All studies evaluating open benign hysterectomies noted a decrease in LOS [12−18]. Mukhopadhyay [12] demonstrated that over time LOS continued to decrease after implementation of an ERAS protocol for open hysterectomies. Median LOS was 5 days before institution of ERAS and then decreased to 4 days in the first year and to 3 days in the second year.…”
Section: Open Hysterectomymentioning
confidence: 99%
See 2 more Smart Citations
“…Results derived from an observational study conducted by Wijk et al revealed that implementation of ERAS protocol leads to a significant increase in the number of patients discharged within 2 days after the surgery [23]. Similarly, Mukhopadhyay reported that in patients undergoing open hysterectomies, LOS decreased from 5 days to 3 days with the implementation of ERAS protocols [24]. Ottensen et al showed that median LOS following vaginal surgery performed for utero-vaginal prolapse was also significantly lower in patients receiving ERAS protocols compared to those receiving conventional care [25].…”
Section: Discussionmentioning
confidence: 99%